HEPATOPROTECTIVE ACTIVITY OF FRUIT AND LEAF EXTRACTS OF FICUS CARICA AND FICUS BENGHALENSIS IN EXPERIMENTAL RATS - H. Nawaz; T. Rehman; H. Shahzad; M. Aslam; I. Ahmad; M. Fatima; A. Ali (Journal of Animal and Plant Sciences, 2024)
Ficus plants have traditionally been used as potential remedies for treating various diseases. Hepatotoxicity is one of the severe threats to human health which must be adequately cured. The study was planned to investigate the hepato-protective potential of methanolic extracts of fruit and leaves of Ficus carica and Ficus benghalensis against carbon tetrachloride (CCl4)-induced hepatotoxicity in an experimental rat model. The study was planned using a randomized control design (RCD). The study included 6 groups of animals (n= 5 per group) having average body weight (220±30 g), out of which 5 groups were treated with CCl4 (15 µL kg-1 body weight), and the remaining one was left as healthy control. Four of the five CCl4-treated groups were administered individually with fruit and leaf extracts (25 mg kg-1 body weight) of F. carica and F. benghalensis, while the fifth was left as CCl4-treated control. The total serum bilirubin (TSB), total serum protein (TSP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) levels of the control group during the treatment period ranged from 0.54±0.16 to 0.59±0.15 mgdL-1, 8.56±0.73 to 8.66±0.75 mgdL-1, 46.00±21.41 to 49.41±22.68 UL-1, 41.6±13.99 to 44.41±13.16 UL-1, and 139.80±28.72 to 145.62±28.82 UL-1, respectively. CCl4 administration significantly (p<0.05) increased the TSB, ALT, AST, and ALP levels in the range of 1.48±0.30-2.30±0.19 mgdL-1, 147.6±34.22 to 233.81±14.94 UL-1, 118.8±15.88 to 167.8±16.4143 UL-1, and 213.8±21.46 to 260±26.664 UL-1, respectively. The elevated TSB, ALT, AST, and ALP levels were significantly (p<0.05) decreased after F. carica and F. benghalens extract treatment to 1.06±0.15-1.70±0.21 mgdL-1, 115.00±28.19-190.21±25.68, 89.8±16.29-111.8±23.81 UL-1, and 195.38±42.29-218.4±35.02 UL-1 respectively. Moreover, TSP level was significantly decreased after CCl4 administration and improved after extract treatment. It was concluded that methanolic extract from the leaf and fruit of both F. benghalensis and F. carica protects against CCl4-induced hepatotoxicity in rats.
Keywords: Hepatoprotective potential; Ficus carica; Ficus benghalensis; Hepatic damage; Experimental rat model